Effectiveness of a 12-week structured training program on performance improvement in recreational male tennis players (NTRP 2.5): Controlled experimental study - Roy Ardian; Qays Banwan Shareef (Journal of Applied Movement and Sport Science, 2025)
Background Low skill levels among beginner recreational tennis players often pose a major obstacle to developing basic techniques, stroke consistency, and understanding of game strategy. This situation can lead to low motivation to play and slow overall performance progress. One potential approach to addressing this issue is through the implementation of a structured, planned training program that takes place over an adequate period of time. Objectives This study aims to test the effectiveness of a 12-week structured tennis training program on improving the performance of male recreational tennis players with a National Tennis Rating Program (NTRP) rating of 2.5. Methods The study uses a quasi-experimental design with 100 participants evenly divided into an experimental group and a control group. The experimental group participated in a structured training program that included basic technique drills, tennis-specific physical training, and game simulations, while the control group only engaged in routine training without a strict structure. Performance data was collected through pre-test and post-test measurements, including shot accuracy, rally consistency, and response speed. Data analysis was performed using paired t-tests, ANOVA, and Cohen’s d effect size calculations. Results The results of the study showed that the experimental group experienced a significant improvement in performance (p < 0.001; d = 1.99) with higher effectiveness compared to the control group (d = 0.72). Conclusion The conclusion of this study is that a structured 12-week tennis training program can significantly improve the basic skills of beginner recreational tennis players. The contribution of this research is to provide a scientific basis for coaches and tennis clubs in designing evidence-based training programs that are effective in accelerating skill development and increasing active participation at the recreational level.